Henry Walter Bates: um viajante naturalista na Amazônia e o processo de transferência da informação - FERREIRA, Rubens da Silva (2014)
From the XVII century on, in the Amazon it began a moving of traveler naturalists as they were attracted by the biosociodiversity of the region, which was dominated by a forest of a tropical type. Henry Bates (1825-1892), a Natural History's scholar, was one of them, though he dislocated to the North of Brazil later on, between the years of 1848 and 1859. In such a context and through this paper, it is intended to analyze the process of transference of information that was produced by this traveler naturalist after 11 years of fieldwork. With basis on the bibliographic material that was selected towards this endeavor, it was verified that such a process was successful as an ample circulation of the Bates' published work reveals it. Exactly after the 156 years of this expedition, the scientific production of Bates continue to participate of the academic knowledge's circuit referring to the Amazon in the contemporary times, be it in the field of the Biology, Zoology, Sociology, History or of the Anthropology.